2016
DOI: 10.1021/acs.macromol.6b00376
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chirality in Achiral Polyfluorene: Chiral Gelation, Memory of Chirality, and Chiral Sensing Property

Abstract: Producing supramolecular chirality from achiral π-conjugated polymers toward preferred chiral memory, effective circularly polarized luminescence, and chiral sensor is extremely important in design of functional chiral materials. Proposed herein is an effective protocol to generate and memorize the supramolecular chirality formed from achiral poly­(9,9-dioctyl­fluorene) (PF8) induced by chiral solvation. The process of chiral supramolecular assembly was monitored by UV–vis spectroscopy, circular dichroism (CD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 78 publications
1
81
0
Order By: Relevance
“…Light is one of the most important stimuli since it is easily controlleda nd is largely nondestructive. [21][22][23][24][25] In order to realize chiroptical switching based on azobenzene, it is important to transfer chirality to the azobenzene moiety,s ince azobenzene itself is achiral.D uring such chiral transfer,s elf-assembly of the component molecules is necessary.H owever,i nm any cases, although strong p-p interactions between azobenzene moieties can assist self-assembly, they often cause irreversibility of the trans-cis isomerization. Photochromic groups, such as azobenzene, spiropyran, or dithienylethene, have been incorporated into the gels through covalent bonds or by as upramolecular approach.…”
Section: Introductionmentioning
confidence: 99%
“…Light is one of the most important stimuli since it is easily controlleda nd is largely nondestructive. [21][22][23][24][25] In order to realize chiroptical switching based on azobenzene, it is important to transfer chirality to the azobenzene moiety,s ince azobenzene itself is achiral.D uring such chiral transfer,s elf-assembly of the component molecules is necessary.H owever,i nm any cases, although strong p-p interactions between azobenzene moieties can assist self-assembly, they often cause irreversibility of the trans-cis isomerization. Photochromic groups, such as azobenzene, spiropyran, or dithienylethene, have been incorporated into the gels through covalent bonds or by as upramolecular approach.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical shift of the TPA aromatic protons of 1 was also larger than that of the terpyridine protons of 1 ( Figure S8), indicating strong p-p stacking between the TPAc omponents (as compared with the terpyridine components). In contrast, the chemical shift of the amide protons of the alanine moiety of 1 in [D 8 ]THF was nearly same as that of the achiral amide protons attached to the TPAc omponent ( Figures 4B,D), suggesting that both chiral and achiral amide moieties formed intermolecular hydrogen bonds with- www.chemeurj.org out any interference of solvent molecules. Additionally,t he chemicals hift of the terpyridine protons was 7-10 times larger than that of the TPAp rotons ( Figure S9).…”
Section: Influence Of Achiral Amide Moieties On the Helicity Of Gel 1mentioning
confidence: 94%
“…[1][2][3][4][5] It plays ak ey role in many advanced functions in life. During the past two decades, there has been considerable researcho n the helicala rchitectureb ecause of its structural beauty,v ital roles in biologicals ystems, [6][7][8] and potentialf or practicala pplication, such as chiral separation [9][10][11][12][13] and asymmetric catalysis. [14][15][16][17][18] The helix is intrinsically chiral and is alwayse ither leftor right-handed.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many diverse factors, such as tersolvent composition, solvent polarity, polymer molecular weight, alkyl chain length, limonene enantiopurity, solution temperature, clockwise and counter-clockwise stirring, and aggregate size are confirmed to influence the magnitude of the induced CD and/or CPL amplitude. Through theoretical calculation, they assume that the inherent twisting ability (H-H repulsion) between the near- Zhang et al demonstrated that solvent chirality can be transferred to the aggregates of many optically inactive π-conjugated polymers with different backbone structures, such as main chain azo-containing polyfluorene (F8AZO), poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PF8), poly(9,9-di-noctylsila-fluorenyl-2,7-diyl) (PSi8), poly(9-(1-octylnonyl)-9H-carbazole-2,7-diyl) (PCz8), P(F8-alt-Si8), P(F8-alt-Cz8), and P(Si8-alt-Cz8), hyperbranched PF8s, side chain azo-containing polymers PAzoMA, P(AzoMA-rans-MMA), and star side-chain Azo polymers (star PAzoMAs) as shown in Figure 6 [69,[72][73][74][75][76]. Optically active F8AZO aggregates were successfully generated by the chirality transfer from (S)-and (R)-limonene, demonstrated by the intense ICD signals corresponding to F8AZO in the visible region [69].…”
Section: Preparation For Optically Active π-Conjugated Polymermentioning
confidence: 99%
“…This novel element-dependent chiroptical inversion and structural dependence of π-conjugated polymers with the help of limonene chirality in aggregation states pave a new way for designing chiroptical functional polymers. Furthermore, they successfully constructed the supramolecular chirality for CDsilent PF8 by cooling its limonene solution at low temperature [74]. More interestingly, the supramolecular chirality can be transferred to solid films and be perfectly memorized.…”
Section: Preparation For Optically Active π-Conjugated Polymermentioning
confidence: 99%